Implementation of The Archipelago Module In Managing Intercultural Conflict - Syafa, Shalsabilla (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
The Indonesian government provides opportunities for students to learn about culture through the Merdeka Student Exchange (PMM) program, which includes academic and non-academic aspects. However, students often face intercultural conflicts due to cultural differences and ways of communicating, especially when interacting with Sundanese culture in West Java. Misunderstandings in communication can hinder adaptation in a new environment. The presence of the Nusantara Module is expected to provide understanding and intercultural communication skills to overcome conflicts and build harmonious relationships. This study aims to analyze and evaluate the implementation of the Nusantara Module in managing intercultural conflicts of PMM 3 Inbound students at the Islamic University of Bandung. The method used is qualitative research with a phenomenological approach, through data collection techniques of observation, interview, and documentation. Informants were determined by purposive sampling, and data analysis using phenomenological techniques by Creswell and Moustakas. The theory used is Face Negotiation Theory by Stella Ting-Toomey, which explains differences in perception in interaction. The results showed that PMM 3 students experienced challenges in managing intercultural conflict, but the Nusantara Module activities significantly improved their awareness and communication skills.